Pengaruh Model Course Review Horay (CRH) Berbantuan Media Question Card Terhadap Hasil Belajar Siswa Kelas IV SD Negeri 10 Toboali - Mohammad Nur Kholis; Feni Kurnia; Rifki Hanif Setiawan (Universitas Muhammadiyah Bangka Belitung, 2026)
The poor learning results in the Natural and Social Sciences (IPAS) subject, notably in the area of Plant Reproduction, served as the impetus for this research. The goal of this study was to assess the impact of the Course Review Horay (CRH) paradigm, supported by Question Card media, on the learning results of fourth-grade students at SD Negeri 10 Toboali. Using a pre-experimental, one-group pretest-posttest approach, this study made use of an experimental technique. The sample comprised 28 fourth graders at SD Negeri 10 Toboali, who were chosen using a saturated sampling method. The test, which consisted of five essay questions on plant reproduction, was used to gather data. The Shapiro–Wilk test for normality and the Paired Sample t-test for hypothesis testing were used to analyze the data. The average posttest score for the students was 87.50, according to the results. The Shapiro-Wilk normality test, which indicated that the data were normally distributed, gave pretest and posttest p-values of 0.088 and 0.103, respectively, both of which were greater than 0.05. The Paired Sample t-test produced a significance value of 0.000, which is less than 0.05. It implies that H0 was turned down and Ha was approved. As a result, it may be inferred that the Course Review Horay (CRH) model, which was backed by Question Card media, greatly improved the learning outcomes of fourth-grade students at SD Negeri 10 Toboali.